Upgrading of Al-Rustamiyah Sewage Treatment Plant Through Experimental and Theoretical Analysis of Membrane Fouling - Ibrahim, Raheek I. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Al-Rustamiyah plant is the oldest and biggest sewage treatment plant in Iraq; it locates in the south of Baghdad city. The plant suffers from serious problems associated with overflow and low capacity. The present work aims to upgrade the heart of biological treatment process through suggesting the use of membrane bioreactor; (MBR). In this work, fouling of membrane during sewage treatment has been analyzed experimentally and theoretically by fouling mechanisms. Aeration has been applied in order to control fouling through producing effective diameters of air bubbles close to the membrane walls. Effect of air flow rate on flux decline was investigated. Hermia’s models were used to investigate the fouling mechanisms. The results showed that cake formation is the best fitted model (R2≥0.98) followed by intermediate blocking occurred with 9 L/min aeration rate. Cake layer formation is the best fit mechanism in all aeration rates (1-9 L/min) in presence of microalgae. SEM images of the membrane surface before and after filtration showed high density pores membrane surface proved a cake fouling occurring. It was found that aeration represents the most effective technique for fouling domination in addition to its important economic aspects for algae growth and propagation. An enhancement of 70.8% in flux at 9 L/min air flow has been revealed. MBR proved to be more efficient and more convenient than activated sludge since it eliminates the needing of sedimentation tanks and upgrading Al-Rustamiyah plant that has low available space for expansion.